PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBASIS PENDEKATAN SAINTIFIK MATERI GETARAN GELOMBANG SISWA KELAS VIII SMP ISLAM PLUS JABAL NOOR - Gustapu, Tri Adi; Laili, Alik Mustafidal (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2025)
The science learning process at SMP Islam Plus Jabal Noor, especially in class VIIIA on vibration and wave material, has so far still used simple media in the learning process and the methods applied, such as lectures and discussions, so that students feel bored and tired in understanding the material. This study aims to develop learning media in the form of animated videos based on a scientific approach to the material of wave vibrations and to determine the level of validity and practicality based on the assessment of media experts and material experts and teacher and student response questionnaires. This study uses the Research and Development (R&D) research method adapted from the ADDIE development model. The results of this study indicate that the level of validity of animated video learning media based on a scientific approach to the material of wave vibrations for class VIII students of SMP Islam Plus Jabal Noor based on the assessment of media experts from both validators is 83.33% with the criteria "valid". Furthermore, the assessment of material experts obtained an average validity from both validators of 82.30% with the criteria "valid". The practicality assessment of the teacher response questionnaire received a score of 90.76%, and from the response questionnaire of class VIIIA students totaling 30 students with an average of 81.58% with the criteria of "very practical". So it can be concluded that the animated video learning media based on the scientific approach of wave vibration material can be used as a learning. ABSTRAKProses pembelajaran IPA di SMP Islam Plus Jabal Noor, khususnya di kelas VIIIA pada materi getaran dan gelombang, selama ini masih menggunaan media sederhana dalam proses pembelajaran serta metode yang di terakpan, seperti ceramah dan diskusi, sehingga peserta didik merasa bosan dan jenuh dalam memahami materi. Penelitian ini bertujuan untuk mengembangkan media pembelajaran berupa video animasi berbasis pendekatan saintifik pada materi getaran gelombang serta untuk mengetahui tingkat kevalidan dan kepraktian berdasarkan penilaian para ahli media dan ahli materi serta angket respon guru dan peserta diidk. Penelitian ini menggunakan metode penelitian Research and Development (R&D) yang diadaptasi dari model pengembangan ADDIE. Hasil penelitian ini menunjukkan bahwa tingkat kevalidan media pembelajaran video animasi berbasis pendekatan saintifik pada materi getaran gelombang siswa kelas VIII SMP Islam Plus Jabal Noor berdasarkan penilaian ahli media dari kedua validator adalah sebesar 83,33% dengan kriteria “valid”. Selanjutnya penilaian ahli materi diperoleh rata-rata kevalidan dari kedua validator adalah sebesar 82,30% dengan kriteria “valid”. Penilaian kepraktisan angket respon guru mendapat nilai 90,76%, dan dari angket respon peserta didik kelas VIIIA berjumlah 30 siswa dengan rata-rata 81,58% dengan kriteria “sangat praktis”. Sehingga dapat disimpulkan, bahwa media pembelajaran video animasi berbasis pendekatan saintifik materi getaran gelombang dapat digunakan sebagai media pembelajaran.